2002
DOI: 10.1111/j.1365-2621.2002.tb10652.x
|View full text |Cite
|
Sign up to set email alerts
|

Use of High‐pressure Processing for Oyster Shucking and Shelf‐life Extension

Abstract: Whole Pacific oysters (Crassostrea gigas) were processed using high-pressure processing (HPP) treatment from 207 to 310 MPa at 0, 1, and 2 min and stored at Ͻ Ͻ Ͻ Ͻ Ͻ 4 Њ Њ Њ Њ ЊC and evaluated over 27 d. The pH of HPP samples decreased slightly from 6.3 to 5.8 during storage while the control (hand-shucked oysters) dropped to pH 4.1. Moisture content of the controls decreased slightly while HPP samples increased slightly. Pressure treatment did not significantly inhibit lipase activity during the shelf-life s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
139
0
3

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 192 publications
(157 citation statements)
references
References 22 publications
15
139
0
3
Order By: Relevance
“…Although the shellfish industry uses HPP at pressures of approximately 300 MPa to facilitate oyster shucking, extend shelf life, and reduce total bacterial counts, including those of Vibrio spp. (19), it is not clear whether the higher pressures required, as suggested by our data, to reduce HuNoV contamination in shellfish will be viable for current commercial units. In addition to evaluation of the upper pressure limits of current commercial units, the consumer acceptability of 600-MPa HPP-treated oysters needs to be investigated.…”
Section: Vol 77 2011 Human Norovirus Inactivation By Hpp 5479mentioning
confidence: 82%
See 1 more Smart Citation
“…Although the shellfish industry uses HPP at pressures of approximately 300 MPa to facilitate oyster shucking, extend shelf life, and reduce total bacterial counts, including those of Vibrio spp. (19), it is not clear whether the higher pressures required, as suggested by our data, to reduce HuNoV contamination in shellfish will be viable for current commercial units. In addition to evaluation of the upper pressure limits of current commercial units, the consumer acceptability of 600-MPa HPP-treated oysters needs to be investigated.…”
Section: Vol 77 2011 Human Norovirus Inactivation By Hpp 5479mentioning
confidence: 82%
“…In general, HPP has been shown to maintain the appearance, flavor, nutritional quality, and texture of raw shellfish (37,43). HPP also serves a practical application by facilitating the shellfish shucking process by separating the meat from the shell and has been demonstrated to extend refrigerated shelf life (14,19,43). HPP has also been identified recently as a potential means for inactivating parasitic and viral pathogens such as Cryptosporidium parvum oocysts (12), hepatitis A virus, and HuNoV surrogates within raw shellfish (9,22,25,54).…”
mentioning
confidence: 99%
“…Some authors showed that the pressure resistance of microbial organisms is maximal at temperature [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] o C and decreases significantly at higher or lower temperature (10,11,12).…”
Section: High Pressure Processing and Microbial Inactivationmentioning
confidence: 99%
“…hydrostatic pressure treatment is also effective in inactivating other hazardous microorganisms such as E. coli, Salmonella, and Vibrio, as well as many yeasts, molds, and bacteria responsible for food spoilage. the microbiological shelf-life and food quality can be substantially extended by the use of hPP (23,24).…”
Section: Introductionmentioning
confidence: 99%
“…HHP is utilized commercially on the United States gulf and western coasts (Gold Seal Oysters Inc., Homa, La., and Nisbet Oyster Inc., Bay Center, Wash.) at pressures of up to 275 megapascals (MPa), principally because it can facilitate the oyster-shucking process and extend the shelf-life of raw oysters due to the reduction of spoilage bacteria (24). Organoleptic evaluations have shown that HHP-treated oysters are acceptable to consumers at treatment pressures as high as 400 MPa or approximately 60,000 lb/in 2 (30).…”
mentioning
confidence: 99%